Pengaruh Model Project Based Learning Terhadap Kemampuan Berpikir Kreatif Peserta Didik Kelas XI IPS Mata Pelajaran Geografi di SMA Negeri 3 Purwokerto - Niken Rimadhona; Dhi Bramasta; Mustolikh Mustolikh (UM Purwokerto Press, 2023)
21st century capabilities explain student-centered learning, teamwork, and learning related to the context of students' daily lives. One of the abilities in the 21st century is the ability to think creatively. This study aims to determine the effect of the learning modelproject based learning on the creative thinking skills of students in class XI IPS at SMA Negeri 3 Purwokerto. This research method namelyPretest-Posttest Control Group design. Test analysis using testpaired simple t-test as a paired two-sample test. Sample test resultspre-test experiment andpost-test experiment has a value of Sig. 000 <0.05 which means that there is an influence of the learning modelProject Based Learning on the creative thinking skills of students in class XI IPS Indonesia at SMA Negeri 3 Purwokerto.